Induction of Neutralizing Antibodies against Diphtheria Toxin by Priming with Recombinant Mycobacterium bovis BCG Expressing CRM(197), a Mutant Diphtheria Toxin - Miyaji, Eliane N. (American Society for Microbiology, 2001)
BCG, the attenuated strain of Mycobacterium bovis, has been widely used as a vaccine against tuberculosis and is thus an important candidate as a live carrier for multiple antigens. With the aim of developing a recombinant BCG (rBCG) vaccine against diphtheria, pertussis, and tetanus (DPT), we analyzed the potential of CRM(197), a mutated nontoxic derivative of diphtheria toxin, as the recombinant antigen for a BCG-based vaccine against diphtheria. Expression of CRM(197) in rBCG was achieved using Escherichia coli-mycobacterium shuttle vectors under the control of pBlaF*, an upregulated β-lactamase promoter from Mycobacterium fortuitum. Immunization of mice with rBCG-CRM(197) elicited an anti-diphtheria toxoid antibody response, but the sera of immunized mice were not able to neutralize diphtheria toxin (DTx) activity. On the other hand, a subimmunizing dose of the conventional diphtheria-tetanus vaccine, administered in order to mimic an infection, showed that rBCG-CRM(197) was able to prime the induction of a humoral response within shorter periods. Interestingly, the antibodies produced showed neutralizing activity only when the vaccines had been given as a mixture in combination with rBCG expressing tetanus toxin fragment C (FC), suggesting an adjuvant effect of rBCG-FC on the immune response induced by rBCG-CRM(197). Isotype analysis of the anti-diphtheria toxoid antibodies induced by the combined vaccines, but not rBCG-CRM(197) alone, showed an immunoglobulin G1-dominant profile, as did the conventional vaccine. Our results show that rBCG expressing CRM(197) can elicit a neutralizing humoral response and encourage further studies on the development of a DPT vaccine with rBCG.